Practices on Waste Disposal and Its Environmental Effects - Aming-Hayudini, Magna Anissa E.; Jaddani, Mohammad Yusof T.; Habibun, Salta I. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study aimed to determine the practices of waste disposal among residents of Barangay Upper Sanraymundo, Jolo, Sulu, Philippines. The researchers sought to answer to the following questions: What is the demographic profile of the resident in terms of educational attainment? What are the practices on waste disposal among the residents? What are the effects on environment of waste disposal practices among the residents? And; is there a significant effect of the waste disposal practices on environment? Quantitative type of research was utilized specifically the descriptive-predictive research method. The researchers made used of self-structured survey questionnaire based from related literature, related studies and validation of experts. Convenience sampling was used in determining the selected 99 respondents out of 8,308 populations of Upper Sanraymundo Jolo, Sulu, Philippines. Based on the findings of the gathered data, it was therefore concluded that majority of the respondents are high school graduates. It was also concluded that the majority of the residents always practice waste disposal. The study also found out that the majority of the respondents are aware about the effect of solid waste if not disposed properly. It also concluded that there is a significant effect of solid waste on environment. Among the findings and conclusions, the highest priority recommendation policies in this study are to strengthen the Republic Act 9003 also known as Ecological Solid Waste Management of 2000 to maintain the necessary policy framework and continue implementing the integrated waste management plan based on 3Rs (reduce, reuse, and recycle) of which the Local Government of Jolo, Sulu, Philippines is strictly complying on the said mandates.